A multifunctional micropore-forming bioink with enhanced anti-bacterial and anti-inflammatory properties. (1st April 2022) - Wang, Mian; Li, Wanlu; Luo, Zeyu; Tang, Guosheng; Mu, Xuan; Kuang, Xiao; Guo, Jie; Zhao, Zhibo; Flores, Regina Sanchez; Jiang, Zewei; Lian, Liming; Japo, Julia Olga; et al.
Abstract: Three-dimensional (3D) bioprinting has emerged as an enabling tool for various biomedical applications, such as tissue regeneration and tissue model engineering. To this end, the development of bioinks with multiple functions plays a crucial role in the applications of 3D bioprinting technologies. In this study, we propose a new bioink based on two immiscible aqueous phases of gelatin methacryloyl (GelMA) and dextran, further endowed with anti-bacterial and anti-inflammatory properties. This micropore-forming GelMA-dextran (PGelDex) bioink exhibited excellent printability with vat-polymerization, extrusion, and handheld bioprinting methods. The porous structure was confirmed after bioprinting, which promoted the spreading of the encapsulated cells, exhibiting the exceptional cytocompatibility of this bioink formulation. To extend the applications of such a micropore-forming bioink, interleukin-4 (IL-4)-loaded silver-coated gold nanorods (AgGNRs) and human mesenchymal stem cells (MSCs) were simultaneously incorporated, to display synergistic anti-infection behavior and immunomodulatory function. The results revealed the anti-bacterial properties of the AgGNR-loaded PGelDex bioink for both Gram-negative and Gram-positive bacteria. The data also indicated that the presence of IL-4 and MSCs facilitated macrophage M2-phenotype differentiation, suggesting the potential anti-inflammatory feature of the bioink. Overall, this unique anti-bacterial and immunomodulatory micropore-forming bioink offers an effective strategy for the inhibition of bacterial-induced infections as well as the ability of immune-regulation, which is a promising candidate for broadened tissue bioprinting applications.